The Validity and Legibility of Digital Literacy-Based Reproductive System Flipbook to Improve The Critical Thinking Skills of Grade 11Th High School Students - Puput Tri Utami; Nur Ducha (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2020)
21st century education has an important role to equip students with how to process and use information critically. This can be realized by developing digital literacy-based learning media, one of them is flipbook. The development of the flipbook in this study was applied to reproductive system material because the basic competence of the material requires analysis of information from various sources. The aim of this study was to produce a valid flipbook of reproductive system which had an appropriate level of legibility. The study used Hannafin and Peck development model which consisted of the needs analysis, design, and development phases. The measured parameters included the validation and legibility level of the flipbook. Validation was done by education expert lecturer, reproductive system expert lecturer, and Biology teacher based on the appropriateness of content, presentation, language, and critical thinking components. while the level of legibility of the flipbook was measured using the Fry formulation by analyzed 100 words in each section. The results of the validation showed very valid categories in each component with the average percentage of the presentation was 87.5%, content eligibility 96.3%, linguistic 91.7% , and critical thinking 98.3%. The validation components got 93.5% average percentage with a very valid category. The level of legibility of the flipbook showed level 11 with the appropriate category for high school students. Based on the results of the study, the developed flipbook was declared to be very valid and had an appropriate level of legibility for high school students. Keywords: digital literacy-based, reproductive system, flipbook, critical thinking skills